The Art of Arriving: A New Methodological Approach to Reframing "Refugee Integration". (15th March 2022) - Mijić, Ana; Parzer, Michael
The main objective of the transdisciplinary and arts-based research project "The Art of Arriving: Reframing 'Refugee Integration'" is to explore the transformative potential of the arts for the sociology of migration and integration. By creating a real-world laboratory where sociologists accompany artists as they create, and recipients while they interpret aesthetic expressions, the project focuses on the process of refugees' arriving. The aim is to examine if and how the meaning-making processes involved in creating and interpreting art can foster alternative views about "refugee integration" and extend or even revise the traditional sociological toolkit for understanding integration. The article discusses the methodological implications of the planned transdisciplinary multimethod approach by paying particular attention to the different logics of knowledge production in science and the arts. Additionally, it sheds light on the benefits associated with the mutual translation between sociology and various fields of art, which is mediated through the process of creating and interpreting aesthetic expressions in the context of refugee migration.